Effect of Non-Genetic Factors on Growth Traits of Kashmir Merino Sheep - Rasool Janbaz, Rakib; Reshi, Parvaiz Ahmed; Ganai, Abdul Majeed; Mir, Abdul Qayoom; Abdullah, Muzamil; Ahmad, Tavsief; Majid, Ruksana; Mir, Mohsin Ayoub (Journal of Livestock Biodiversity, 2025)
The study investigates the influence of non-genetic factors viz. Period and season of birth, sex, parity and birth type, on growth traits of Kashmir Merino sheep reared under the temperate agro-climatic conditions of Kashmir. Growth performance records collected over a nine year period (2016 - 2024) at the Mountain Research Centre for Sheep & Goat (MRCSG), SKUAST-K, were analyzed using a fixed linear model in R package. Traits included birth weight (BW), weaning weight (WW), six-month weight (6M) and twelve-month weight (12M). The average BW, WW, 6M and 12M weights were estimated as 3.71±0.06 kg, 13.13±0.29 kg, 22.97±0.41 and 30.28±0.89 kg with coefficients of variation of 21.29 %, 18.74%, 17.94% and 21.33%, respectively. The overall least-squares means were 3.5 ± 0.129 kg, 14.6 ± 0.667 kg, 22.1 ± 0.916 kg, and 33.9 ± 2.38 kg for BW, WW, 6M and 12M, respectively. Period of birth, Season of birth, parity, sex and birth type significantly influenced the growth traits in Kashmir-Merino Sheep. The study highlights the importance of accounting for these non-genetic factors in growth performance evaluation.